TRIZ and MACBETH in Chemical Process Engineering - João, Isabel (2017)
The Chemical Process Industry (CPI) is facing an increasing pressure to develop new or improved chemical processes. The major challenges experienced by CPI is related with sustainability namely economic, social, and environmental issues, is the reason why innovation in chemical process design is becoming more challenging. However innovative chemical process design needs the support of a systematic innovation approach to guide engineers in the creation of new or improved chemical processes. The objective of this work is to present an approach that integrates the theory of inventive problem solving (TRIZ) and a multicriteria decision analysis method MACBETH for the selection of an improved chemical design among different options. The objective is to establish a systematic innovation approach to assist engineers or decision makers through the idea generation with TRIZ theory, and use MACBETH to perform the selection of the best-generated concept. The use of a combined approach in chemical process improvement may increase the efficiency of concept selection avoiding time waste. An illustration is presented in order to show the simplicity and applicability of the approach.